Internal Control Analysis of the Vendor Accounts Payable Payment System at Hotel XYZ - KAMELIA, Annisa Fitri; NUGROHO, Herbirowo (PT Keberlanjutan Strategis Indonesia, 2025)
The hotel industry is one of the service industries that has high operational activities, including procurement transactions for goods and services made by purchasing on credit, resulting in debt. At Hotel XYZ, the vendor debt payment system plays an important role in maintaining smooth operations and cooperative relationships with suppliers. However, there are still problems in the form of late payments that can interfere with operational continuity and vendor confidence. This study aims to analyze internal control in the vendor payable payment system at Hotel XYZ and evaluate weaknesses to provide recommendations for improvement. This research uses a qualitative method with a case study approach and data collection techniques in the form of interviews, observations, and documentation. The results showed that Hotel XYZ has implemented most of the elements of internal control, such as organizational structure, tiered authorization, the use of sequentially numbered documents, and the use of the Power Pro system for recording transactions. However, there are still weaknesses such as duplication of duties, delays in manual authorization, and the absence of automatic reminders of payment due dates. Therefore, it is necessary to strictly separate functions, digitize the authorization process, and implement a reminder system to improve the quality of internal control.